G84(P) The importance of time elapsed since an episode of alleged child sexual abuse in the discovery of positive findings on later examination. (May 2019) - Woolley, EA; Teebay, L
Abstract : Aims: To determine whether the time elapsed since an episode of alleged child sexual abuse is important for discovering positive physical findings, in relation to the type of abuse, gender and pubertal stage of the child. Method: The medical records of 796 children seen over a 7 ½ year period who were consecutively referred to a specialist paediatric sexual assault referral centre for suspected sexual abuse were evaluated. The variables extracted were time elapsed since latest episode of abuse to examination (<24 hours, 24–72 hours, 3–7 days, 7–14 days, 14–21 days, >21 days), gender, pubertal stage of child (pre, peri and post pubertal), type of abuse (penetrative and touching, if known) and physical findings on anogenital examination. Results: After exclusion criteria were applied, the data from 543 records were analysed. Abnormal anogenital examination findings were present in 191 (35.2%) patients. Over half the patients (51.4%) were seen within 72 hours. The prevalence of positive findings was higher when patients were seen within that period; 44.7% at <24 hours (72/161) and 40.7% between 24–72 hours (48/118) compared to those seen at later time intervals; 22.5% between 3–7 days (18/80), 25% between 7–14 days (8/32) and 22.2% between 14–21 (4/18). Other variables which were also seen to have an impact on discovery of positive findings were 1. Gender : female vs male patients (36.9%, 167/453 vs 26.7%, 24/90). 2. Type of abuse: penetrative vs touching abuse (38%, 159/408 vs 7.1%, 4/56). 3. Pubertal stage: in post-pubertal vs pre-pubertal females who were examined past the 21 day period (44.2%, 23/52 vs 20.5%, 9/44). Conclusion: Positive findings are more likely to be present on earlier examination, with pre-pubertal children in particular being more likely to have positive anogenital findings identified when seen within 72 hours. These findings highlight the importance of a specialist paediatric forensic examination either by a forensic paediatrician or jointly with a paediatrician and forensic physician of the patient as soon as possible after the alleged abuse is suspected or disclosed.